Production of functional human galectin-1 in transplastomic tobacco and simplified recovery via batch-mode purification - Vater, Catalina Francisca; Pérez Sáez, Juan Manuel; Stupirski, Juan Carlos; Massaro, Mora; Mirkin, Federico Gabriel; Bravo-Almonacid, Fernando Félix; Rabinovich, Gabriel Adrián; Morgenfeld, Mauro Miguel (Frontiers in Plant Science, 2026)
Plant molecular farming has established itself as a transformative technology for the cost-effective and sustainable production of biopharmaceuticals, offering scalable solutions to meet growing global demand. Among the different stable plant expression systems, plastid-based platforms are particularly attractive due to their high recombinant protein accumulation potential, genetic stability, and reduced risk of transgene escape. Human Galectin-1 (hGAL1) is a β-galactoside-binding lectin with potent immunomodulatory properties, positioning it as a promising therapeutic candidate for autoimmune and inflammatory diseases. Preserving its native conformation and carbohydrate-binding capacity is essential to keep its biological activity, and both properties may be compromised under suboptimal expression or purification conditions. Here, we demonstrate the relevance of chloroplast transformation in Nicotiana tabacum as a platform for producing functional hGAL1, which accumulated up to 5.67 mg per kg of leaf tissue, corresponding to ~0.05% of total soluble protein (TSP). Using a simplified batch-mode purification strategy, intact hGAL1 retaining carbohydrate-binding activity was obtained and functional properties as shown by its ability to induce T cell apoptosis in a dose-dependent manner. These results highlight the potential of a transplastomic tobacco platform to deliver biologically active human lectins with therapeutic relevance, while minimizing downstream processing complexity, supporting their use in cost-effective biopharmaceutical production.